Labor Exclusion and the Erosion of Citizenship Responsibilities - Ronconi, Lucas (2015)
This paper shows that workers who do not receive legally mandated benefits due to employer noncompliance take a negative perspective not only toward the employer as it has been documented but also against the state. They consider that the state did not protect their rights, and hence feel fewer obligations to comply with their duties as citizens. Using a list experiment, as well as household data from nine Latin American countries, we show that nonregistered workers are less likely to obey the law, pay taxes, and vote compared to registered workers.